Apresentação do dossiê “Cultura e educação na América Portuguesa" / Presentation of the dossier "Culture and education in Portuguese America" - Lage, Ana Cristina Pereira (Revista de História e Historiografia da Educação, 2020)
Revista de História e Historiografia da Educação v. 3, n. 7 / 2019